1997
DOI: 10.1177/109019819702400305
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Perceived Risk and Health Behavior: A Critical Review of HIV Prevention Research

Abstract: Perceived risk of infection, one factor influencing HIV-related behavior decisions, has been the focus of expanding research efforts. A body of research now exists examining factors related to risk perceptions and the relationship between risk perceptions and behavioral decision making. This article examines 60 quantitative studies of HIV-related risk perceptions, identifies methodological and theoretical limitations or gaps in current knowledge, and suggests ways future research might better assess the role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
78
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 78 publications
3
78
0
1
Order By: Relevance
“…Risk perception forms an important component in many models aiming to understand health risk behaviors. Previous research has shown that perceptions of HIV risk are affected by multiple factors including: History of injecting drug use, number of sexual partners, and HIV-related knowledge (Kalichman, Hunter, & Kelley, 1992;Kowalewski, Henson, & Longshore, 1997). That women in both the national and local samples who reported HAS also reported higher perception of risk for HIV is cause for concern.…”
Section: Hypothesis 5 Women Who Report Has Have a Lower Perception Ofmentioning
confidence: 86%
“…Risk perception forms an important component in many models aiming to understand health risk behaviors. Previous research has shown that perceptions of HIV risk are affected by multiple factors including: History of injecting drug use, number of sexual partners, and HIV-related knowledge (Kalichman, Hunter, & Kelley, 1992;Kowalewski, Henson, & Longshore, 1997). That women in both the national and local samples who reported HAS also reported higher perception of risk for HIV is cause for concern.…”
Section: Hypothesis 5 Women Who Report Has Have a Lower Perception Ofmentioning
confidence: 86%
“…Sources of normative messages about sex also include religious groups and the mass media (Brewster, Cooksey, Guilkey, & Rindfuss, 1998;Keller & Brown, 2002;Zaleski & Schiaffino, 2000). Social norms are said to have substantial impact on the motivation to practice safe sex and to abstain from risky sexual behavior (Hynie, Lydon, Cote, & Wiener, 1998;Kowalewski, Henson, & Longshore, 1997;Stanton et al, 2002;Zaleski & Schiaffino, 2000). Studies have shown condom use to be strongly affected by peer norms about condom use (Ford & Wirawan, 2002;Latkin,, Forman, Knowlton, & Sherman, 2003) and perceptions of peer condom use (Stanton et al, 2002), although among some groups, perceptions of peer condom use may not be as important (Brown et al, 2004).…”
Section: Social Normsmentioning
confidence: 95%
“…In the United States overall, estimates of the prevalence of HIV among MSM fall between 9% (Xu, Sternberg, & Markowitz, 2010) and 19% (Centers for Disease Control and Prevention, 2010), suggesting that the majority of participants in this study overestimated national HIV prevalence. Evidence from prior research indicates that people are inaccurate at estimating the probability of rare events (Kowalewski et al, 1997), often relying on heuristics. The increased odds of perceiving higher HIV prevalence among participants in older agegroups, for instance, may reflect the influence of the availability heuristic (Tversky & Kahneman, 1973); men in older age-groups are more likely to have encountered more people with HIV/AIDS, which has been reported to increase perceptions of prevalence and personal risk (Downing et al, 2001;Klepinger et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has pointed to the influence of constructs such as self-efficacy, perceived behavioral control, perceived benefit from testing, and perceived severity of HIV infection (Albarracín et al, 2001;Floyd et al, 2000;Janz & Becker, 1984;Lau et al, 2012), which were not assessed in this study. Many subjective factors also influence perceptions of the risk posed by specific partners, including physical attractiveness and the level of intimacy and trust (Agocha & Cooper, 1999;Kowalewski et al, 1997;Lorenc et al, 2011;Mitchell & Horvath, 2013;Schmälzle, Renner, & Schupp, 2012). Furthermore, the decision to test may not be rational.…”
Section: Discussionmentioning
confidence: 99%